Relationship between Social Media for Social Marketing in Family Planning - Ardiansyah, Ardiansyah (UI Scholars Hub, 2021)
This research aims to examine the influence of marketing mix carried out media performance social media portal on attitude towards a social marketing program,and its relationship with source credibility of the portal. This study was focused on